Vitamin intake in obesity and hypertension: A population-based study from Haryana, North India - Neha Yadav; Vineet Chaudhary; Kallur Nava Saraswathy; Naorem Kiranmala Devi (Elsevier, 2022)
Background: Obesity and hypertension are two highly prevalent health conditions and important risk factors for several health adversities. Adequate intake of certain vitamins has been reported to play a protective role in obesity and hypertension. Since dietary pattern, among other factors, delineates the status of vitamin intake in a population, it is pertinent to validate the relationship between vitamin intake, obesity, and hypertension in populations with unique dietary patterns. This study aimed to explore the interrelationship between intake of selected vitamins, obesity, and hypertension among adults of a lacto-vegetarian population. Methods: A total of 488 participants, aged 30-70 years of either sex, were recruited from Palwal, Haryana, India. Data on socio-demographic variables and dietary intake was collected using a pretested interview schedule & food-frequency questionnaire (FFQ) respectively. Body mass index (BMI), and blood pressure (BP) were determined using standard techniques. Statistical analysis was performed using SPSS. Results: While inadequacy in vitamin B9 intake was found to be positively associated with hypertension, inadequate vitamin C intake was found to be positively associated with both overweight/obesity and hypertension. In stratified analyses for BMI and BP categories, adequate intake of vitamin B9 and C was found to be protective against hypertension only among non-overweight/obese individuals; however, regardless of BP status, adequate vitamin C intake was inversely associated with overweight/obesity. Conclusions: Adequate intake of vitamin C can help in reducing the burden of obesity in general and hypertension among non-obese individuals. Further, adequate intake of vitamin B9 may be protective against hypertension.